Odpowiedź:
a) [tex]6 \frac{7}{9} - \frac{1}{3} = 6 \frac{7}{9} - \frac{3}{9} = 6 \frac{4}{9} = 6 \frac{2}{3}[/tex]
b) [tex]5 \frac{1}{4} - \frac{5}{8} = 5 \frac{2}{8} - \frac{5}{8} = \frac{42}{8} - \frac{5}{8} = \frac{37}{8} = 4 \frac{5}{8}[/tex]
c) [tex]1 \frac{1}{2} - \frac{5}{9} = \frac{3}{2} - \frac{5}{9} = \frac{27}{18} - \frac{10}{18} = \frac{17}{18}[/tex]
d) [tex]7 \frac{3}{4} - 5 \frac{7}{9} = \frac{31}{4} - \frac{52}{9} = \frac{279}{36} - \frac{208}{36} = \frac{71}{36} = 1 \frac{35}{36}[/tex]
Mam nadzieję, że pomogłam :)